Pendampingan Kampanye Anti Perundungan di Sekolah Menengah Pertama Negeri 1 Taliwang - Minten Ayu Larassati; Fitria Yuliana; Hari Asgar (Jurnal Pemberdayaan Masyarakat, 2026)
Community Service activities were carried out at SMP Negeri 1 Taliwang. The purpose of this activity is to raise students' awareness of the dangers of bullying behaviours and actions, as well as to serve as a real effort and concrete step to build a safe and inclusive school culture for all students. The challenges and problems faced by SMP Negeri 1 Taliwang as a partner are the low level of student understanding regarding the forms of bullying, the impact of bullying, and the ways and methods that can be employed to prevent bullying behaviours in the school environment. Schools serve as a small replica of society, acting as an inclusive space for students. Some methods that can be used include interactive socialisation, group discussions, and guidance for anti-bullying campaigns which can be realised through creative media such as posters and educational videos. The results of the activities conducted showed an increase in students' knowledge and positive attitudes towards efforts to prevent bullying and acts of violence occurring in the school environment.